Intellectual Property Rights, Multinational Firms and Technology Transfers - Sara Biancini; Pamela Bombarda (Center for Economic Studies and ifo Institute (CESifo), 2017)
Intellectual Property Rights (IPR) protect firms from imitation and are considered crucial to promote innovation and technological diffusion. This paper examines the impact of IPR on import sourcing decisions of multinationals. We consider a framework in which firms offshore production of an intermediate good in a developing country. Firms can either decide to import the intermediate from vertically integrated producers, or from independent suppliers. In both cases, offshoring part of the production process embodies a risk of imitation. The model predicts that, under reasonable assumptions, stronger IPR encourage by a larger extent the imports of intermediates through vertical integration. Using U.S. Related-Party Trade database, we find empirical evidence supportive of the positive link between level of IPR and the relative share of imports from vertically integrated manufacturers.
Keywords: F12; F23; O34; 330; intellectual property rights; MNF; FDI; outsourcing; international trade